Pengaruh Stabilitas Penjualan, Struktur Aktiva DanTingkat Pertumbuhan Terhadap Struktur Modal (Studi Empiris Terhadap Perusahaan Real Estate and Property yang Terdaftar di BEI Tahun 2007-2009) - Vitriasari, Ririn; Indarti, Iin (Jurnal Kajian Akuntansi dan Bisnis, 2012)
The purpose of this study was to determine the influence of the stability ofsale, asset structure, growth rate on capital structure of Real Estate and Property companieslisted in Indonesia Stock Exchange in 2007-2009. This research used quantitative research,thatis a research that uses numbers, ranging from data collection, interpretation of data, as well asthe appearance of the results. In this research, the data used was secondary data, the data inthe form of financial statements of Real Estate and Property companies listed in IndonesiaStock Exchange in 2007-2009. The method for sample selection used non probability samplingmethod for purposive sampling with consideration of which the samples were not randomlyselected and the information obtained by certain considerations. The population was 50companies and the samples were 27 companies. Based on the processed data, it generated n =27 x 3 = 81, but when there was outlier, the samples became 74 companies. The samplingtechniques for data analysis was multiple linear regression.The result of stability of sale was 1.191, assets structure was -1.649, growth rate was -1.204and t table was 1.9949. if t value < t table then Ho was received and Ha was rejected. So all thevariables simultaneously did not have a positive influence on capital structure. The result of Fvalue was 1.938 and F table was 2.50 with n = 74. Coefficient of determination value was 0.126or 12.6%. This means that 12.6% variation of the variable of capital structure can be explainedby three variables. While the rest (100% - 12.6% = 87.4%) is explained by other variablesbesides variable of stability of sale, asset structure and growth rates.Keywords : Stability of sale, Esset Structure, Growth Rate, Capital Structure